Morphology test of activated charcoal from oil palm fronds with H2SO4 and NaOH activators - Debby Marantika; Masthura Masthura; Ratni Sirait (Universitas Riau, 2024)
Activated charcoal has been investigated by utilizing oil palm fronds using the addition of H2SO4 and NaOH activators. The purpose of this study was to determine the microstructure of the effect of activated charcoal using H2SO4 and NaOH activator at a carbonization temperature of 500°C for 60 minutes. The method used in this research is a method with a quantitative approach. The characterization used was scanning electron microscopy to determine the surface morphology of activated charcoal. The results of the tests carried out for the H2SO4 and NaOH activators showed that the best results were found in the NaOH activator which had larger pores than the H2SO4 activator, with a particle diameter size range of 0.432 – 1.564 µm which was analyzed using software Digimizer.